Crustal assimilation in arc magmas controlled by overriding plate thickness - Chiaradia, Massimo (Frontiers in Earth Science, 2025)
Magmas erupting in arcs range in composition from MgO-rich basalt to MgO-poor rhyolite. This broad compositional range is due to the sequential crystallization and separation of minerals with different chemical compositions from the cooling magma (a process known as fractional crystallization), to mixing between magmas that have undergone different degrees of fractional crystallization, and to the assimilation of rocks, in which high temperatures allow magmas to partially melt and assimilate them. Although the roles of fractional crystallization and mixing in arc magmas have been addressed on a large scale, the role of crustal assimilation has mostly been assessed at local to regional scales and not at the global scale. Using published whole-rock geochemical data on 18 modern arcs of variable crustal thicknesses (∼10–∼65 km), this study highlights that correlations of elements (MgO and Co), which are the indices of fractional crystallization, with Nd and Sr isotopes, which are the tracers of assimilation, change systematically in magmatic rocks with the crustal thickness of the arc. These correlations indicate the occurrence of assimilation–fractional crystallization (AFC) processes in arcs of different crustal thicknesses. Based on the results of geochemical modeling, the systematics of the correlations between Sr–Nd isotopes and MgO–Co suggest that the rate of crustal assimilation during fractional crystallization of the magmas increases as the thickness of the arc crust becomes greater, which is a consequence of both these processes occurring at deeper and hotter crustal levels in a thick crust compared to a thin crust. In addition, the rocks that are assimilated by arc magmas in increasingly thick arcs are isotopically more evolved, suggesting that the process of crustal growth, refining, and maturation in arcs results from a continuous reworking of previously formed crust through time by subsequent arc magmatic events.